2003
DOI: 10.4049/jimmunol.170.9.4840
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine on HIV Envelope Is a Cofactor for Infection of Monocytic Cells

Abstract: HIV-1 is an enveloped retrovirus that acquires its outer membrane as the virion exits the cell. Because of the association of apoptosis with the progression of AIDS, HIV-1-infected T cells or macrophages might be expected to express elevated levels of surface phosphatidylserine (PS), a hallmark of programmed cell death. Virions produced by these cells would also be predicted to have PS on the surface of their envelopes. In this study, data are presented that support this hypothesis and suggest that PS is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 56 publications
(51 reference statements)
7
117
0
Order By: Relevance
“…By contrast, we propose that TIM-1 accomplishes this task by association of its PS-binding domain located in the IgV domain with the PS exposed on the envelopes of the budding virions. Consistent with this model, PS has been shown to be exposed on the surface of HIV-1 as well as some other viruses (34)(35)(36). Furthermore, we show here that TIM-1 mutants, which are deficient in PS binding, cannot effectively block HIV-1 release, do not induce PS flipping, yet are incorporated into HIV-1 virions.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…By contrast, we propose that TIM-1 accomplishes this task by association of its PS-binding domain located in the IgV domain with the PS exposed on the envelopes of the budding virions. Consistent with this model, PS has been shown to be exposed on the surface of HIV-1 as well as some other viruses (34)(35)(36). Furthermore, we show here that TIM-1 mutants, which are deficient in PS binding, cannot effectively block HIV-1 release, do not induce PS flipping, yet are incorporated into HIV-1 virions.…”
Section: Discussionsupporting
confidence: 67%
“…Viral infection has been shown to induce PS flipping to the outer leaflet of the plasma membrane, accounting for, at least in part, PS exposure on the surface of viral particles (34)(35)(36). We thus examined if expression of TIM-1 induces PS redistribution on the cell membrane, and if so, whether or not this would be important for the TIM-1 inhibition of HIV-1 release.…”
mentioning
confidence: 99%
“…In this study, we have shown that the depletion and inhibition of the biosynthesis of cholesterol by treatment with M␤CD and lovastatin, respectively, impaired GP64-dependent internalization but not the binding of the viruses. Phosphatidylserine (PS), which is localized in the inner plasma membrane, is known to be exposed on the envelopes of viral particles of vaccinia virus and HIV (10,46). Morizono et al reported that the serumsoluble protein Gas6 binds to both PS on viral particles and TAM receptor tyrosine kinase Axl on target cells and mediates virus binding by bridging the virus to target cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylcholine accounts to 75% of total phospholipid [85] GP Viral envelopes are enriched in sphingomyelin [8,86] SP Envelope cholesterol is critical for structure and infectivity [87][88][89] ST 2 Phosphatidylserine stimulates entry of enveloped viruses [90,91] Mannose receptor binds to the ManLAM mannose caps of mycobacteria and mediates phagocytosis [92] GPI anchored proteins (host [35,36] and parasite [37] …”
Section: Glmentioning
confidence: 99%